Epidemiology and likelihood of asymptomatic malaria among community dwellers in the Fanteakwa south district of Ghana - Enoch Aninagyei; David Adedia; Gifty Larbi; Stella Omane Acheampong; Margaret Nyarko; George Abeiku Abbew; Isaac Tuwarlba; Desmond Omane Acheampong (Parasite Epidemiology and Control)
Background: Data on the asymptomatic burden of malaria in endemic areas is essential for Ghana's malaria elimination efforts. Consequently, the situation of asymptomatic malaria in the Fanteakwa South District (FSD) is determined in this study. The FSD is predominantly forested with more rural than peri-urban communities. Additionally, artisanal mining is prevalent in the district. Despite that the forgoing could promote high incidence of malaria, the burden of asymptomatic malaria and associated factors in the district have never been determined. Methods: This community-based cross-sectional study was conducted in four randomly selected communities in the FSD in the Eastern region of Ghana. The participating households were systematically selected, of which one household member was randomly enrolled in the study. With prior consent, 2 mL of whole blood was collected from the participants. Subsequently, the study variables were obtained from the enrolees using a structured questionnaire. The malaria status of the enrolled participants was determined using the CareStart™ malaria rapid diagnostic test kit (mRDT) (USA). The multiple logistic regression model was used to fit the model to predict the groups at risk of P. falciparum infection in the district. Results: In total, 412 study participants were enrolled. The overall prevalence of asymptomatic malaria in the district was 43.4 % (179/412). The prevalence rate was 36.9 %, 27.7 %, 50 % and 58.8 % (<0.001) respectively for the Dwenase, Bosusu, Nsutam and Osino communities. Living at Bosusu (p = 0.045, AOR = 0.23, 95 % CI: 0.05–0.96), Dwenase (p < 0.001, AOR = 0.12, 95 % CI: 0.04–0.30) and Nsutam (p < 0.001, AOR = 0.19, 95 % CI: 0.08–0.45) were less likely to contract malaria compared to Osino dwellers. Furthermore, pregnant women (p = 0.024, COR = 0.35, 95 % CI: 0.14–0.9) and individuals who do not share mosquito nets with others (p = 0.017, COR = 0.47, 95 % CI: 0.25–0.88) were less likely to contract malaria. Moreover, being an adolescent (p = 0.048, COR = 1.93, 95 % CI: 1.00–3.73), living in mining communities (p = 0.002, COR = 1.97, 95 % CI: 1.27–3.05), being nocturnally active (p = 0.001, AOR = 4.64, 95 % CI: 1.97–11.31), living in a medium quality house (p = 0.031, AOR = 2.31, 95 % CI: 1.09–5.00), schooling in the district (p < 0.001) and body temperature above >37.5 °C (<0.001), were predictors of asymptomatic malaria. Conclusions: The burden of asymptomatic malaria is high in the Fanteakwa South district. In this context, the implementation of the ‘mass strategy’ recommended by the World Health Organization will play a key role in eliminating malaria in the district.